The Role of Technical Guidance And Training on the Performance of Educators in Improving Student Learning Achievement - Budi Harsono (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to determine the significant influence of the role of technical guidance and training on the performance of educators in improving the quality of student learning. This study uses quantitative methods, with the object of this research being teachers and students of elementary school. Data collection techniques using questionnaires, interviews, and direct observation of schools. The results of hypothesis testing indicate that the first hypothesis (H1), namely technical guidance has an effect on teacher performance, is accepted because it has a p-value of 0.000 or 0.05 which is significant. The second hypothesis test (H2), namely the training variable that affects teacher performance, has a p-value of 0.000 which is significant because the value is 0.05. Technical guidance and training activities can improve teacher competence so that the teaching performance of teachers is getting better and ultimately student learning achievement can be improved.